Chana striata Albumin Gel Accelerate Post tooth extraction Wounds Healing on Hyperglycemic Rats - Indraswary, Recita; Muchaeroni, Isa Anshori; Ardlina, Nira; Amrullah, Alex (Odonto : Dental Journal, 2024)
Background: Hyperglicemic patients with type 2 diabetes often experience slow wound healing due to poor neovascularization, macrophages and fibroblast, therefore, medicine is needed to speed up the wound healing process, one of which is albumin. Albumin is a protein that has been shown to have antioxidant properties and also plays a role in accelerating the inflammatory process and stimulating the growth of new cells.Method: This research used laboratory experiments and a Post Test Only Control Group Design research design. The number of research samples used was 26 wistar rats, snakehead fish albumin gel extract is made by maceration and gelled using CMC (Carboxyl methyl cellulose), assessment method by observing fibroblasts, neovasculature and macrophages which are visible in Hematoxylin Eosin and toluidine blue staining.Result: The results of the research showed that the group that was given snakehead fish albumin extract gel had a higher average number of neovascular, macrophage and fibroblast values than the group that was not given snakehead fish albumin extract gel. The Mann Whitney test and Independent Sample T-Test showed that there were significant differences between the 2 groups.Conclusion: The conclussion from this research is there is an effect of gived snakehead fish albumin gel on tooth extraction wounds in Diabetes Mellitus rats